2018
DOI: 10.1002/admi.201800031
|View full text |Cite
|
Sign up to set email alerts
|

Carbonized Bamboo‐Derived Carbon Nanodots as Efficient Cathode Interfacial Layers in High‐Performance Organic Photovoltaics

Abstract: have been demonstrated as efficient IFmodified layer for OPV applications, [2] including self-organized molecules, [3] conjugated materials, [2b] ionic compounds (e.g., electrolytes), [4] metal oxides, [1g,5] and nonconjugated organic materials. [6] Typically, the mechanism through which the PCE is improved relies on (i) passivation of interfaces to suppress carrier recombination, [7] (ii) enhanced carrier extraction, [8] (iii) enhancing interfacial dipoles and modifying the work function (built-in dipole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…To circumvent these issues related to grain boundaries defects and to optimize the morphology of the perovskites, here we studied the effects of CNDs—rich in hydrogen bonding units and having a highly conjugated carbon structure—and urea as additives and explored their abilities to interact intermolecularly with MAPbI 3 and, thereby, enhance the performance of the resulting PSCs. We prepared the CNDs according to a procedure we had described previously; they exhibited high photoluminescence and an average particle size of ≈3–5 nm . As displayed in Figure a, the CNDs were rich in COOH groups and were highly conjugated; furthermore, urea is an efficient Lewis base.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To circumvent these issues related to grain boundaries defects and to optimize the morphology of the perovskites, here we studied the effects of CNDs—rich in hydrogen bonding units and having a highly conjugated carbon structure—and urea as additives and explored their abilities to interact intermolecularly with MAPbI 3 and, thereby, enhance the performance of the resulting PSCs. We prepared the CNDs according to a procedure we had described previously; they exhibited high photoluminescence and an average particle size of ≈3–5 nm . As displayed in Figure a, the CNDs were rich in COOH groups and were highly conjugated; furthermore, urea is an efficient Lewis base.…”
Section: Resultsmentioning
confidence: 99%
“…Yang and co‐workers used CNDs as electron modifying layers and obtained a PSC demonstrating a PCE of 19% . In a previous study, we reported the use of carbonized bamboo‐derived CNDs as ZnO modifiers for OPV applications; the carboxylic acid (COOH) and hydroxyl (OH) group‐rich CNDs modified the work function of the ZnO and optimized the blend morphology, resulting in high‐performance OPVs . Because of the functionality of these CNDs (rich in hydrogen bonding groups; highly conjugated structures), we suspected that we could also employ them as additives for PSCs ( Figure 1 a).…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative of fossil fuel-based energy sources, numerous nanoscale materials have been used in the fabrication of highly efficient, green, low cost and scalable photovoltaic devices, especially solar cells (SCs). 2,29,[147][148][149][150][151][152][153][154][155][156] To date, most of the SCs (such as organic SCs, silicon based SCs, and dye/QD-sensitized SCs (DSSCs/QDSSCs)) are based on the use of toxic nanomaterials, with a lack of scalability, renewability and maximum power conversion efficiency. 2,29,[147][148][149][150][151][152][153][154][155][156] In this regard, the ecofriendly, inexpensive biomolecule-based C-QDs and G-QDs, with the scope of scalability and renewability and alluring optical features, have started to gain interest due to their different photovoltaic activities, such as sensitizers and photoabsorption agents (due to their absorption tail in the visible zone), charge carrier sources, and bridges and funnels (due to their large p-electron network (sp 2 core) and electron donating and accepting capability).…”
Section: Solar Cells and Energy Conversionmentioning
confidence: 99%
“…2,29,[147][148][149][150][151][152][153][154][155][156] To date, most of the SCs (such as organic SCs, silicon based SCs, and dye/QD-sensitized SCs (DSSCs/QDSSCs)) are based on the use of toxic nanomaterials, with a lack of scalability, renewability and maximum power conversion efficiency. 2,29,[147][148][149][150][151][152][153][154][155][156] In this regard, the ecofriendly, inexpensive biomolecule-based C-QDs and G-QDs, with the scope of scalability and renewability and alluring optical features, have started to gain interest due to their different photovoltaic activities, such as sensitizers and photoabsorption agents (due to their absorption tail in the visible zone), charge carrier sources, and bridges and funnels (due to their large p-electron network (sp 2 core) and electron donating and accepting capability). 2,29,[147][148][149][150][151][152][153][154][155][156] Importantly, the use of man-made material-based C-QDs and G-QDs has been displayed to have applicability in developing heterojunction solar cells devices (ZnO QDs/G-QDs and CDs/Si: with enhanced absorption and suppressed recombination and thus higher efficiency compared to their parent components), open circuit voltage increment in devices (depending on the quantum size effect of the G-QDs), solution-processed organic/metal oxide and dyesensitized solar cells (such as combination of poly(3hexylthiophene) (P3HT) and GQDs, and TiO 2 with G-QDs and...…”
Section: Solar Cells and Energy Conversionmentioning
confidence: 99%
“…1 CDs exhibit strong and tunable uorescence properties, high photostability, and unique photoluminescence behaviors. 2,3 By virtue of these distinct optical benets, CDs show a variety of applications in uorescent ink, 4 bioimaging, 5 drug delivery 6 as well as sensing. [7][8][9][10] However, the relatively low quantum yield (QY) of nonfunctionalized CDs, usually consisting of carbon and oxygen elements, is usually a limiting factor for their wider applications.…”
Section: Introductionmentioning
confidence: 99%